Web-Based Ordering Management System - Tham, Si Si (2003)
With the huge grow of the Internet, the traditional way of ordering system may not be effective and efficient to handle the sales order and there are highly human dependent. So, Web-based Ordering Management System is a great way of business to promote them as it enables them to communicate their message directly to the target customer. This project aims to deliver an efficient and effective system to replace the traditional way of ordering system. With this Web-based Ordering Management System enable the customer to order their preference products through web. Besides that, this project also aims to develop a low cost, easy to maintain and user-friendly windows based Ordering Management System for Health Care Product Company in Malaysia.